Residue, dissipation, and dietary intake evaluation of fenpyroximate acaricide in/on guava, orange, and eggplant under open field condition - Malhat, Farag; Abdallah, Osama; Anagnostopoulos, Chris; Hussien, Mohamed; Purnama, Indra; Helmy, Rania M. A.; Soliman, Hanim; El-Hefny, Dalia (Frontiers in Nutrition, 2022)
Fenpyroximate is a widely used acaricide applicable in many crops. In this study, the residue behavior of fenpyroximate on eggplant, orange and guava was investigated. The chronic and acute dietary intake was calculated at several sampling points, and preharvest intervals were proposed to ensure compliance with the existing maximum residue levels. A simple extraction protocol combined with ultrahigh-performance liquid chromatography–tandem mass spectrometry was employed to quantify residue levels. The method was successfully validated according to EU guidelines, and a limit of quantification of 0.01 mg/kg was set. The dissipation patterns in all crops could be described by the first-order kinetics model with half-lives of 1.7, 2.2, and 1.9 days for eggplants, guavas and oranges, respectively. The dietary risk assessment at the authorized or more critical application patterns was acceptable for the consumers. For oranges and eggplant, a PHI of 3 and 7 days, respectively, can be proposed; however, a proposal was not possible for guava due to the absence of maximum residue limits and quantitative residue findings at all sampling points tested. The current work not only contributes to the practical application of fenpyroximate related to residue management in dryland areas such as Egypt but can also be used to estimate the appropriate PHIs and support the authorization of plant protection products as supplementary information.